The Influence of Empowerment, Supply Chain Strategy, and Job Involvement toward Professional Commitment - Pakpahan, Faurna Lusiani; Madhakomala, Madhakomala; Purwarna, Dedi (International Journal of Supply Chain Management, 2020)
Abstract- The impact of the supply chain management (SCM) greatly influences the form of professional commitment that has a good impact toward its institution. The objective of this research was to find out and to analyze the influence of empowerment, supply chain management, and job involvement toward professional commitment through the company system. The sample of this research was taken by using proportional random sampling. The samples were the Women Navy Corps consisted of 160 respondents from the total of 250 Women Navy Corps. In this research, the researchers used Structural Equation Model in testing, analyzing the data, and model development. The Data were analyzed by using statistical software tools (LISREL 8.8). The results were: 1) Empowerment has a positive direct influence toward personality, 2) Empowerment has a positive direct influence toward professional commitment, 3) Supply chain management has a positive direct influence toward personality, 4) Supply chain management has a positive direct influence toward professional commitment, 5) Job involvement has a positive direct influence toward personality, 6) Job involvement has a positive direct influence toward professional commitment, 7) Personality has a positive direct influence toward professional commitment, 8) Empowerment has a positive indirect influence toward professional commitment through personality, 9) Supply chain management has a positive indirect influence toward professional commitment through personality, and 10) Job involvement has a positive indirect influence toward professional commitment through personality.